Automatic Identification of Experts and Performance Prediction in the Multimodal Math Data Corpus through Analysis of Speech Interaction - LUZ, SATURNINO (ACM Press, 2013)
An analysis of multiparty interaction in the problem solving sessions of the Multimodal Math Data Corpus is presented. The analysis focuses on non-verbal cues extracted from the audio tracks. Algorithms for expert identification and performance prediction (correctness of solution) are implemented based on patterns of speech activity among session participants. Both of these categorisation algorithms employ an underlying graph-based representation of dialogues for each individual problem solving activities. The proposed Bayesian approach to expert prediction proved quite effective, reaching accuracy levels of over 92\% with as few as 6 dialogues of training data. Performance prediction was not quite as effective. Although the simple graph-matching strategy employed for predicting incorrect solutions improved considerably over a Monte Carlo simulated baseline (F1 score increased by a factor of 2.3), there is still much room for improvement in this task.
Proceedings of the 15th ACM on International conference on multimodal interaction, ICMI'13 - Grand Challenge on Multimodal Learning Analytics
ICMI'13
PUBLISHED
Keywords: Machine Learning; Multimodal Interaction; Dialogue; Learning Analytics; Intelligent Content & Communications